100 .найдите производные: f`(0), если f(u)=1/(u^2+3u+2)f`(-1), если f(u)=√(5x^2+2x+1)f`(1), если f(x)=√e^xнайти производную: s = \frac{2}{ \sqrt{t} } - \frac{3}{ \sqrt[3]{t} }

макс3013 макс3013    2   07.03.2019 10:51    1

Ответы
Scruff17 Scruff17  24.05.2020 19:15
Заменяю u и t на х для удобства

1) \: f'(x) = \frac{ - 2x - 3}{ {( {x}^{2} + 3x + 2)}^{2} } \: \: \: \: f'(0) = - \frac{3}{4} \\ \\ 2) \: f'(x) = \frac{10x + 2}{2 \sqrt{5 {x}^{2} + 2x + 1 } } \: \: \: \: f'( - 1) = \frac{ - 4}{ \sqrt{4} } = - 2 \\ \\ 3) \: f'(x) = \frac{ {e}^{x} }{2 \sqrt{ {e}^{x} } } = \frac{ \sqrt{ {e}^{x} } }{2} \: \: \: \: f'(1) = \frac{ \sqrt{e} }{2} \\ \\ 4)f'(x) = - \frac{1}{2} \frac{2}{ {x}^{ \frac{3}{2} } } - ( - \frac{1}{3} \frac{3}{ {x}^{ \frac{4}{3} } } ) = \frac{1}{ {x}^{ \frac{4}{3} } } - \frac{1}{ {x}^{ \frac{3}{2} } }
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра